GEOMETRIC SHAPES STUDY IN A WARI POTTERY IN THE MIDDLE HORIZON OF MANTARO VALLEY, PERU - Altamirano Enciso, Alfredo (2014)
The present work concernsto analysis of geometric forms showed in a zooanthropomorfized pottery of Middle Horizon (Wari) of Mantaro Valley. Our methodology was to use a new focus own of Andean World (like a textile method) to understand the tripartition spaces of Kay Pacha, Uku Pacha and Hanan Pacha. However, up, middle and dawn are ordered in relation to head, body and inferior members. This structural method permitted to recognize the metaphoric philosophy. However, anterior/posterior (face/back) and up/below are instruments of this duality of opposition and complementary. We recognize 32 symbols starting of geometric forms like circle with points, ovals, triangles, sinuosoids, white spotsradial, colors, steps and curves. Then these signs are confronted with some cosmogonic myths to reach the symbolic means related to origins of corn, potatoes, mountain and waters. Finally, we conclude that there is two gods that opposed and complement: Illapa and Pachamama.